The wonky donkey - Smith, Craig, 1972-; Cowley, Katz, 1973- (New York : Scholastic, 2010)
Illustrations and lyrical text describe a bird's adventure walking down the road and meeting an odd donkey with three legs and one eye.
2.6
K-3.
K-3
English
Keywords: Birds -- Songs and music -- Texts; Children's songs; Donkeys -- Songs and music -- Texts; Birds -- Songs and music; Donkeys -- Songs and music; Songs; Birds -- Songs; Donkeys -- Songs; Songs; Picture books for children